2018
DOI: 10.1159/000488721
|View full text |Cite
|
Sign up to set email alerts
|

Disease Burden, Psychological Well-Being and Attitudes regarding the Set of Emergency Medication in Adults with Insect Venom Allergy

Abstract: Background: Insect venom allergy is common and greatly impairs patients’ quality of life. Additionally, low compliance with carrying emergency medication is reported. The aim of our study was to analyze the disease burden, levels of anxiety and depression, and to evaluate attitudes towards the set of emergency medication in affected patients. Methods: Between April 2016 and January 2017, patients ≥18 years visiting our department because of an insect venom allergy were asked to complete a paper-based questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Female HVA patients have a higher subjective anxiety level than male patients and are more inclined to carry the EMS "always" or "almost always" with them, but have lower self-assurance in using it. In our previous analysis of our study data, we did not find significant differences regarding anxiety and depression levels between female and male HVA patients in the HADS-A and HADS-D [8]. Interestingly enough, when asked to define their subjective anxiety level due to the venom allergy on a VAS (0 = not anxious at all, 10 = extremely anxious), female patients had a mean value of 7.2, while the mean score in men was 4.6.…”
Section: Participantscontrasting
confidence: 43%
See 1 more Smart Citation
“…Female HVA patients have a higher subjective anxiety level than male patients and are more inclined to carry the EMS "always" or "almost always" with them, but have lower self-assurance in using it. In our previous analysis of our study data, we did not find significant differences regarding anxiety and depression levels between female and male HVA patients in the HADS-A and HADS-D [8]. Interestingly enough, when asked to define their subjective anxiety level due to the venom allergy on a VAS (0 = not anxious at all, 10 = extremely anxious), female patients had a mean value of 7.2, while the mean score in men was 4.6.…”
Section: Participantscontrasting
confidence: 43%
“…Studies investigating for an association between HVA and quality of life as well as patients' compliance with the prescribed EMS are sparse. Thus, in our previous study, we investigated the disease burden, psychological well-being, and attitudes regarding the set of emergency medication in 55 HVA patients [8]. Here, HVA was associated with a moderate disease burden and good compliance with carrying the emergency medication.…”
Section: Introductionmentioning
confidence: 99%
“…Cohort stringency concerning age, gender, and insect allergy is provided compared to other cohorts. 25 , 29 Whereas in the present population the number of female patients slightly prevails, epidemiologic data show a higher prevalence of sensitization to hymenoptera venom in males. 30 The rate of patients allergic to either bee or yellow jacket venom can vary depending on the degree of exposure.…”
Section: Discussionmentioning
confidence: 65%
“…However, the distinct and rather small sample sizes might be a possible confounder, and we suggest a reevaluation with a bigger cohort. As for anxiety, ambiguous findings exist in terms of its correlation with severity of the anaphylactic reaction: while Schaarschmidt et al 29 did not find an association between these parameters, Cichocka-Jarosz et al 32 revealed a significant correlation in their cohort. Still, we conclude that treatment indications for VIT should not only be based on the severity of the reaction, but should also include an assessment of the QoL.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation